Morphological description of the final instar larvae of Argia reclusa Selys, 1865 and Tigriagrion aurantinigrum Calvert, 1909 from Southeastern Brazil (Odonata: Coenagrionidae) - Vilela, Diogo Silva; Venâncio, Henrique; Santos, Jean Carlos (Zootaxa, 2021)
The final instar larvae of Argia reclusa Selys, 1865 and Tigriagrion aurantinigrum Calvert, 1909 are described, diagnosed and illustrated. The larvae of A. reclusa has a very prominent premental ligula, shared with a single species in Brazil, from which it can be separated by a combination of characters. The larvae of T. aurantinigrum is similar to most Oxyagrion in regard to prementum and lamellae shape, and differs from those taxa in palpal and premental setation and number of teeth on the labial palp. Both larvae were collected in a small stream of the Cerrado biome, where both species are common.